1985
DOI: 10.1021/j100249a032
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio STO-nG Hartree-Fock-Roothaan calculations of the ammonia-formic acid complex as a model for hydrogen bonding in crystalline amino acids

Abstract: to form sheets parallel to a crystallographic plane, with the alkyl substituents on the nitrogen atoms essentially perpendicular to the sheets.Along any chain, acfiacent NH+---0 hydrogen bonds are separated by about 6.5 A. The zwitterion dipole moment vectors are inclined at alternating angles of +9 and -9°to the chain axis, with |9| ~20°. For such a lattice, electrostatic calculations in the point-dipole approximation20 have shown that dipole-dipole interactions are energetically very important within a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The temperature of total conversion of the neutral form to the zwitterion depends also on the compound studied, being 275 K for DMG, 200 K for sarcosine and 180 K for glycine. This is in consonance with a greater stability of neutral N-alkyl substituted amino acids in solid state compared with the more ionic non-N-alkylated amino acids having higher melting points, as suggested by Parra-Mouchet et al 46 Finally, in order to obtain further support for the importance of local heating effects in determining the amount of neutral species trapped in the low-temperature solid films, we have also increased the temperature of the substrate and noticed that at a temperature near that at which after annealing of the film deposited at 9 K only zwitterions were observed, no neutral form could be trapped.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The temperature of total conversion of the neutral form to the zwitterion depends also on the compound studied, being 275 K for DMG, 200 K for sarcosine and 180 K for glycine. This is in consonance with a greater stability of neutral N-alkyl substituted amino acids in solid state compared with the more ionic non-N-alkylated amino acids having higher melting points, as suggested by Parra-Mouchet et al 46 Finally, in order to obtain further support for the importance of local heating effects in determining the amount of neutral species trapped in the low-temperature solid films, we have also increased the temperature of the substrate and noticed that at a temperature near that at which after annealing of the film deposited at 9 K only zwitterions were observed, no neutral form could be trapped.…”
Section: Resultssupporting
confidence: 79%
“…Being a measure of the relative stability of the neutral form in the solid state, the temperature of total conversion of the neutral forms to the zwitterions was found to increase with the number of methyl substituents at the nitrogen atom (DMG > sarcosine > glycine), as it could be expected. 46 The whole set of data here obtained indicates that, with all probability, during deposition of the vapour of the compounds, the neutral form first aggregates and then uses the available energy to irreversibly convert, in the solid state, to the therein most stable zwitterionic species.…”
Section: Discussionmentioning
confidence: 79%
“…This was found, for instance, for glycine [16,17], and a-and b-alanine [18]. However, it is also well known that, contrarily to more sophisticated methods, low-level Hartree-Fock calculations in general predict the isolated zwitterionic forms of simple amino acids as being minima on the corresponding PES [19,20]. This is nowadays known to be an erroneous prediction of such low-level calculations, but it has the advantage of enabling theoretical predictions of vibrational spectra (among studied properties that are only meaningful when calculated for stationary points on the PES) to be made.…”
Section: Introductionmentioning
confidence: 93%
“…First, the zwitterionic form of serine, which is the relevant species in solution, is not a minimum energy structure on the potential energy surface of the isolated molecule [26]. Indeed, for the isolated molecule of serine, like for other simple amino acids, it has been shown that the zwitterion is only obtained as a minimum energy configuration when the calculations are performed at a very low level of theory, as a result of an inadequate description of the electronic structure of the system [27][28][29]. Second, the methods available for the indispensable consideration of the solvent have not yet proved to provide results with the desired accuracy: in this case, continuum methods do not seem to be appropriate, considering the essentially specific nature of the water/serine interactions [30][31][32], and severe constraints must still be applied to use solvent discrete models to treat a system of this size, strongly limiting their predictive capabilities.…”
Section: Resultsmentioning
confidence: 99%